The collapse of American criminal justice - Stuntz, William J. (Belknap Press of Harvard Univ. Press)
Introduction: the rule of too much law -- Crime and punishment -- Two migrations -- "The wolf by the ear" -- The past -- Ideals and institutions -- The Fourteenth Amendment's failed promise -- Criminal justice in the gilded age -- A culture war and its aftermath -- Constitutional law's rise, three roads not taken -- Earl Warren's errors -- The rise and fall of crime, the fall and rise of criminal punishment -- The future -- Fixing a broken system -- Epilogue: taming the wolf -- Note on sources and citation form